Systematic Insight of Resveratrol Activated SIRT1 Interactome through Proximity Labeling Strategy - Tian Su; Zhengyi Zhang; Xiao Han; Fei Yang; Zhen Wang; Ying Cheng; Huadong Liu (MDPI AG, 2022)
SIRT1 functions by regulating the modification of proteins or interacting with other proteins to form complexes. It has been widely studied and found to play significant roles in various biological processes and diseases. However, systematic studies on activated-SIRT1 interactions remain limited. Here, we present a comprehensive SIRT1 interactome under resveratrol stimulation through proximity labeling methods. Our results demonstrated that RanGap1 interacted with SIRT1 in HEK 293T cells and MCF-7 cells. SIRT1 regulated the protein level of RanGap1 and had no obvious effect on RanGap1 transcription. Moreover, the overexpression of Rangap1 increased the ROS level in MCF-7 cells, which sensitized cells to resveratrol and reduced the cell viability. These findings provide evidence that RanGap1 interacts with SIRT1 and influences intracellular ROS, critical signals for mitochondrial functions, cell proliferation and transcription. Additionally, we identified that the SIRT1-RanGap1 interaction affects downstream signals induced by ROS. Overall, our study provides an essential resource for future studies on the interactions of resveratrol-activated SIRT1. There are conflicts about the relationship between resveratrol and ROS in previous reports. However, our data identified the impact of the resveratrol-SIRT1-RanGap1 axis on intracellular ROS.